Ethnicity and media: a study of English and non-English language print media coverage of water issues in Sydney. Issue 5 (4th May 2019) - Yan, Liping; McManus, Phil; Duncan, Elizabeth
ABSTRACT: It is critical to understand how matters relating to water are reported, or ignored, among linguistically diverse media and to understand the possible influence this may have on the conception of water issues among ethnically diverse groups. This research analysed five daily newspapers published in Sydney between 2011 and 2012 in three languages (English, Chinese and Korean) and found that water issues were presented differently by newspapers across language divides in Sydney. These differences may contribute to diverse conceptual constructions of water problems and water management among ethnically diverse communities. After allowing for the influence of other variables, this research highlights the necessity to investigate media construction of water issues in various Non-English language publications as an important approach to improving situated and place-based water awareness in an ethnically diverse city.